Unique transcriptional and protein-expression signature in human lung tissue-resident NK cells - Nicole Marquardt (Nature Portfolio, 2019)
Detailed characterizations of human lung tissue-resident natural killer (trNK) cells, which potentially regulate local immune responses, is still lacking. Here the authors show that lung CD69+ CD16– NK cells express tissue-residency markers, produce effector cytokines, and are distinct, feature-wise, from lung CD8+ memory T cells or trNK in other tissues.